Insecticidal Potential of an Orally Administered Metabolic Extract of Aspergillus niger on Chrysomya chloropyga (Green bottle fly) Larvae - J P Essien (Journal of Applied Sciences and Environmental Management, 2005)
The insecticidal activity of Aspergillus niger IHCS-4 metabolic extract against Chrysomya chloropyga larvae was examined in vitro. The toxicity test revealed that 0.04 mg/g and 0.08 mg/g extract concentration significantly (P>0.05) affected the insect larvae, inducing 20% and 65% mortality respectively, within 24 hours. Larval growth was inhibited only at concentrations of 0.04mg/g or higher. Survivors of the toxicity treatment at 0.04mg/g and 0.08mg/g recorded significant reductions in weight over time. These observations have indicated the potential of A. niger as a simple, inexpensive and accessible source of bioinsecticide.